Cardiovascular effect of discontinuing statins for primary prevention at the age of 75 years: a nationwide population-based cohort study in France. (30th July 2019) - Giral, Philippe; Neumann, Anke; Weill, Alain; Coste, Joël
Abstract: Aims: The role of statin therapy in primary prevention of cardiovascular disease in persons older than 75 years remains a subject of debate with little evidence to support or exclude the benefit of this treatment. We assessed the effect of statin discontinuation on cardiovascular outcomes in previously adherent 75-year-olds treated for primary prevention. Methods and results: A population-based cohort study using French national healthcare databases was performed, studying all subjects who turned 75 in 2012–14, with no history of cardiovascular disease and with a statin medication possession ratio ≥80% in each of the previous 2 years. Statin discontinuation was defined as three consecutive months without exposure. The outcome was hospital admission for cardiovascular event. The hazard ratio comparing statin discontinuation with continuation was estimated using a marginal structural model adjusting for both baseline and time-varying covariates (cardiovascular drug use, comorbidities, and frailty indicators). A total of 120 173 subjects were followed for an average of 2.4 years, of whom 17 204 (14.3%) discontinued statins and 5396 (4.5%) were admitted for a cardiovascular event. The adjusted hazard ratios for statin discontinuation were 1.33 [95% confidence interval (CI) 1.18–1.50] (any cardiovascular event), 1.46 (95% CI 1.21–1.75) (coronary event), 1.26 (95% CI 1.05–1.51) (cerebrovascular event), and 1.02 (95% CI 0.74–1.40) (other vascular event). Conclusion: Statin discontinuation was associated with a 33% increased risk of admission for cardiovascular event in 75-year-old primary prevention patients. Future studies, including randomized studies, are needed to confirm these findings and support updating and clarification of guidelines on the use of statins for primary prevention in the elderly.